(untitled) (Journal of Hama University, 2024)
The occlusal plane constitutes a basic physiological concept of the jaw-occlusal relationship. In the lower and upper jaw there are reference points that can be used to determine the occlusal plane, but each method has its own limitations that limit its use. As a method for determining the occlusal plane, therefore, relying on some facial measurements resulting from extra-oral anatomical points may be a way to determine the anterior and posterior occlusal planes in the upper jaw more accurately. Purpose: This research aims to study the relationship between facial height and anterior and posterior occlusal planes in normal people. Materials and Methods: The sample included 100 people who had complete, natural teeth (50 males and 50 females) between the ages of (21_30) years, and using the digital scale, the following measurements were made: The face height, the distance from inner canthus to the anterior occlusal plane, the distance from outer canthus to the posterior occlusal plane were taken. These the corresponding equations have been obtained for each measurement. The results were analyzed using Student’s T test for independent samples, Pearson’s correlation coefficient, one-sided analysis of variance test, based on a confidence level of 95% and a significance level of 5%. Results: The statistical study showed a linear correlation between face height and distances and that the best equation that can be used is the one corresponding to the entire research sample. Conclusions: The relationship resulting from measuring the height of the face and its relationship with the measurements representing the occlusal planes can be used as a method that can be used to guide the anterior and posterior occlusal planes.